P-Glycoprotein Function in Peripheral Blood Mononuclear Cells of Myasthenia Gravis Patients Treated with Tacrolimus - Tanaka, Sachiko; Saito, Toyokazu; Wakata, Nobuo; Hirano, Toshihiko; Oka, Kitaro (Biological & pharmaceutical bulletin, 2007)
Tacrolimus hydrate (FK506) reduces the symptoms of myasthenia gravis (MG) due to its immunosuppressive properties. A drug efflux pump P-glycoprotein (P-gp) actively transports FK506 out of target cells, thereby reducing their efficacy. We investigated the influence of FK506 therapy on the P-gp function of peripheral-blood mononuclear cells (PBMCs) in MG patients. Six MG patients treated with FK506 (MG(FK+)), four MG patients treated without FK506 administration (MG(FK−)), and 18 healthy subjects were included in this study. P-gp function was estimated by transporter activity that was inferred from a decrease in fluorescent P-gp substrate Rhodamine 123 (Rh123) and its inhibition by cyclosporine A (CsA). The P-gp efflux function in MG (FK+) patients assessed by the Kolmogorov–Smirnov (KS) statistic D was lower than in the healthy subjects (p=0.0084). However, PBMC sensitivity to FK506 in MG (FK+) patients was significantly higher compared to that of the healthy subjects (p=0.02). There was a significant correlation between the Rh123 efflux activity and PBMC sensitivity to FK506 in vitro (p=0.011). The data raise the possibility that FK506 treatment attenuated P-gp function in the PBMCs of the MG patients.